2016
DOI: 10.1016/j.spinee.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Combining neuroprotective agents: effect of riluzole and magnesium in a rat model of thoracic spinal cord injury

Abstract: Our results suggest that the combined treatment, although simultaneously targeting two excitotoxic-related mechanisms, did not further improve behavioral and histologic outcome when compared with riluzole given alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 201 publications
(223 reference statements)
0
41
0
Order By: Relevance
“…; Vasconcelos et al . ). The two studies using mm 2 data showed that, with riluzole treatment, there was tissue preservation up to 1.5 mm from the damage epicenter (Simard et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…; Vasconcelos et al . ). The two studies using mm 2 data showed that, with riluzole treatment, there was tissue preservation up to 1.5 mm from the damage epicenter (Simard et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Vasconcelos et al . ), and the remaining studies used an aneurysm clip compression method (Schwartz and Fehlings ; Satkunendrarajah and Fehlings ; Wu et al . ; Can et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although current therapies, such as novel drugs [1] or neurorehabilitation [2] have been developed to treat Spinal Cord Injury (SCI), these therapies could not achieve radical cure. Cell-based therapy using Mesenchymal Stem Cells (MSCs) has been gaining attention as a novel approach to treat the damage caused by SCI.…”
Section: Introductionmentioning
confidence: 99%